An improved artificial fish swarm algorithm for traffic signal control. (26th March 2020) - Lu, Bin; Wang, Qiang; Wang, Yang
The excessive growth of car ownership has caused great pressure on urban traffic. The traffic congestion is the most acute problem. One of the main causes of traffic congestion is the unreasonable scheme of traffic signal timing at road intersections. In view of the limitation of Webster algorithm, we combine the artificial fish swarm algorithm, chaos search and feedback strategy based on the optimisation theory of the signal timing problem to solve this problem. Furthermore, we apply the algorithm to the field of the traffic signal control. We set the average of vehicle delays and parking numbers as the target and improve the target road intersection timing scheme by using the optimisation algorithm. This method enhances the capacity of the target intersection effectively. Taking the condition of the target road intersection and the basic data into consideration, we construct the simulation model of the road intersection through the VISSIM simulation modelling tool. Then we import the relevant data and obtain a new timing plan which sets a new cycle and the green light duration of each phase. Compared to the original method, the algorithm based on the artificial fish-swarm is feasible and effective.